If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 8y + -4x = 0 Reorder the terms: 7x + -4x + 8y = 0 Combine like terms: 7x + -4x = 3x 3x + 8y = 0 Solving 3x + 8y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8y' to each side of the equation. 3x + 8y + -8y = 0 + -8y Combine like terms: 8y + -8y = 0 3x + 0 = 0 + -8y 3x = 0 + -8y Remove the zero: 3x = -8y Divide each side by '3'. x = -2.666666667y Simplifying x = -2.666666667y
| 4(6+x)=-44 | | -68=4x-4(4x-7) | | -10+7=47 | | 7+6=117 | | 2x+2x=6 | | 32*1/8 | | 5w^3-3=0 | | -9x-5/5=8 | | p-8/-4=7 | | 1/2(x+1)+x=5 | | 2=7d-5 | | x=22/3x1/4 | | 4861/24-3584/24 | | w/3-5=4 | | 6(n-3)-2n=10 | | 10-n/3=18 | | 3x-3=10x-55 | | x/-3=-8 | | ((4x)/(x-4))-(4/(x-2))=-2 | | 8(x+7)=7(x+8)+x | | 42+6x=180 | | 8(x+7)=7(x+8)+m | | ((4x)/(x-4))-(4/(x-2)) | | 80x*26*40x= | | -1/3+y=-2/7 | | 2x^(-1/3)-2=0 | | 27/9(3)-2 | | 5x+x=7x | | 5x+12-8x=18-14x+11x-6 | | 1012/3+1383/4+1195/8 | | (4x/x-4)-(4/x-2) | | -2/x^3=0 |